Morphological characteristic analysis of unrecorded freshwater diatoms in Korea - Daeryul Kwon; Kyeong-Eun Yoo; Hyeonjin Cho; Sukmin Yun; Chaehong Park (Applied Microscopy)
Abstract Diatoms are microalgae with a significant ecological role as primary producers, contributing approximately 20% of global carbon fixation. They exhibit remarkable evolutionary success and biodiversity, with approximately 18,000 species identified globally, including 2,323 species reported in Korea. In this study, we identified 13 unrecorded diatom species from various freshwater environments in Korea, including rivers, streams, reservoirs, and lagoons. Among these, the genera Brachysira, Gomphonella, and Staurophora were recorded for the first time in Korea, expanding the national species list. The unrecorded species included 12 pennate diatoms (Adlafia multnomahii, Encyonema cespitosum, Placoneis symmetrica, Gomphonema incognitum, Rhoicosphenia baltica, Brachysira vitrea, Gomphonella fogedii, Hantzschia psammicola, Hyalosynedra laevigata, Pseudostaurosira parasitica, Tryblionella calida, and Staurophora amphioxys) and one centric diatom (Discostella lacuskarluki). Morphological and ultrastructural analyses were conducted using scanning electron microscopy to characterize these species. This research highlights the biodiversity of Korean diatoms and their potential applications in environmental monitoring and nanotechnology, contributing to the broader understanding of diatom taxonomy and ecology.